Antara Rehabilitasi dan Pengulangan Kejahatan: Analisis Pola Pembinaan Residivis di Rutan - Zulfikar Zulfikar; Elvi Susanti Syam; Tegar Bimantoro; Armin Hasti (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2026)
The study examines the implementation and effectiveness of inmate development programs at Rumah Tahanan Negara (Rutan) Kelas IIB Barru in preventing recidivism within Indonesia’s correctional system, which has shifted from a retributive prison model to a rehabilitation-oriented “pemasyarakatan” paradigm grounded in Pancasila and the 1945 Constitution. Using an empirical legal research method with social and case approaches, this research analyzes how structured stages of personality and self-reliance training, as well as religious and skills-based programs, are applied to both first-time offenders and repeat offenders. The findings indicate that although Rutan Barru formally implements a tiered pattern of coaching (initial, advanced, and final stages), the absence of differentiated treatment for recidivists, limited relevance of vocational training to labor market needs, and institutional constraints arising from its dual function as both Rutan and de facto Lapas reduce the overall impact on reducing repeat offending. Recidivism is shown to result from a combination of internal factors (age, low legal awareness, weak religiosity, distorted perceptions) and external factors (family dysfunction, economic hardship, social stigma, and prisonization effects), which hinder social reintegration despite the existing coaching efforts. The study concludes that more targeted, needs-based, and collaborative rehabilitation programs supported by families, communities, and a more humanistic legal framework are required to effectively prevent reoffending and realize the goals of the national correctional system.